The Influence of Access Speed, Transaction Security When Shopping, and Unexpected Value on Digital Customer Delight in Generation Z - Afiat, Dominica Dini; Irdiana, Sukma; Sutjiatmo, Bayu Prabowo; Kusnadi, Iwan Henri; Arief, Ilham; Sidjabat, Sonya (Journal of Information System, Technology and Engineering, 2026)
Digital consumer behavior has changed because of Generation Z which requires companies to build customer satisfaction together with digital customer delight as their main competitive advantage. The research investigates how access speed and shopping transaction security and unexpected value impact digital customer delight for Generation Z users. The study used quantitative research methods to conduct its research through explanatory research design. The researchers conducted a survey which collected data from 220 Generation Z digital users who participated through purposive sampling. The researchers performed data analysis using multiple linear regression after conducting validity testing and reliability testing and classical assumption tests. The study results show that access speed and transaction security together with unexpected value lead to digital customer delight. Access speed functions as a technical factor which improves efficiency together with flow experience while transaction security establishes trust and psychological comfort and unexpected value serves as the primary emotional factor which creates positive surprises and unforgettable moments. The study results show that Generation Z people experience delight through their technology use and their access to security measures together with the experiential marketing elements. The research outcomes provide digital companies with marketing system design and strategy development guidance which will enhance customer satisfaction and create enduring customer loyalty.